Improving hydrogen evolution activity of perovskite BaTiO3 with Mo doping: Experiments and first-principles analysis. (3rd May 2019) - Xie, Pengcheng; Yang, Fan; Li, Renjie; Ai, Changzhi; Lin, Chunfu; Lin, Shiwei
Abstract: Hydrogen production through photocatalytic water splitting attracts great attention in fields of energy conversion. To improve the hydrogen evolution efficiency, narrowing the bandgap of photocatalysts by introducing dopant atoms is widely investigated for increasing light absorption. Herein, Mo-doped BaTiO3 samples are synthesized by a traditional solid-state reaction method and all the samples are modified with Pt by a photo-reduction method. Compared with pure BaTiO3, Mo doping into BaTiO3 samples realizes the band-to-band visible-light absorption and shows remarkable improvement in hydrogen production efficiency. Under simulated sunlight irradiation and with 0.4 wt% Pt deposition, BaTiO3 doped with 2 at% Mo exhibits a hydrogen evolution rate of 63 μmol g −1  h −1, about 2 times improvement in comparison to pure BaTiO3 (35 μmol g −1  h −1 ). Further first-principles calculations based on density-function theory demonstrates an apparent downward movement of the conduction band minimum due to the coupling between the Ti 3d and Mo 3d states, leading to the significant bandgap narrowing and enhancement of the visible-light photocatalytic activity. Graphical abstract: Image 1 Highlights: Enhanced H2 evolution activity is demonstrated in perovskite BaTiO3 by Mo doping. Both experiments and first-principles analysis clarify the improving mechanism. Introduction of Mo atom into BaTiO3 realizes band-to-band visible-light absorption. Coupling of Mo 3d states with BaTiO3 CBM accounts for enhanced HER activity.